2004
DOI: 10.1002/ar.a.20082
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkeratosis in cystathionine beta synthase‐deficient mice: An animal model of hyperhomocysteinemia

Abstract: Cystathionine beta synthase (CBS) is a crucial regulator of plasma concentrations of homocysteine. Severe hyperhomocysteinemia due to CBS deficiency confers diverse clinical manifestations. Patients with severe hyperhomocysteinemia have fine hair and thin skin, but it is unclear whether these changes are related to CBS deficiency or are coincidental. To investigate these aspects of hyperhomocysteinemia, we characterized skin abnormalities of CBS-deficient mice, a murine model of severe hyperhomocysteinemia. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Facial alopecia is the most striking phenotype of Cbs −/− mice on RD, occurring between 105–120 days of age in both males and females (Robert et al 2004; Gupta and Kruger 2011). Previously, we have shown that MRD completely eliminated the facial alopecia phenotype in Cbs −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Facial alopecia is the most striking phenotype of Cbs −/− mice on RD, occurring between 105–120 days of age in both males and females (Robert et al 2004; Gupta and Kruger 2011). Previously, we have shown that MRD completely eliminated the facial alopecia phenotype in Cbs −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some patients with homocystinuria have other skin abnormalities, such as hypopigmentation (129). Similarly, cbs Ϫ/Ϫ mice have hyperkeratosis, wrinkled skin, and an abnormally thin dermal layer (134). Fibrosis and collagen disruption have also been reported in other studies using various tissues from CBS-deficient mice, and this phenotype is not tissue specific.…”
Section: Skin and Skeletal Phenotypes Of Cbs Deficiencymentioning
confidence: 94%
“…Knockout mouse pathogenesis CBS [137][138][139][140] Hyperhomocysteinemia Hyperkeratosis MAT1A 89 Spontaneous hepatocellular carcinoma and impaired liver regeneration MTHFR 85,141 Hyperhomocysteinemia (À/+ and À/À) Developmental retardation with cerebellar pathology (À/À) Aortic lipid deposition (À/+ and À/À) Abnormal spermatogenesis (À/À) FOLR1 (Folbp1 Embryonic lethality (À/À) mouse homolog) 90 reversed by folinic acid supplementation of (À/+) dams…”
Section: Genementioning
confidence: 99%